A new hydrazide functionalized Schiff’s base derivative: Insights into crystallography, Hirshfeld surface, and energy framework analysis - Malviya, Vivek Prakash; Dutta, Archisman (European Journal of Chemistry, 2022)
A new hydrazide functionalized Schiff’s base derivative, N’-(3,4-dichlorobenzylidene)-4-hydroxybenzohydrazide (I), has been synthesized using a solvent-assisted mechano-chemical grinding strategy and structurally characterized using elemental analysis, 1H NMR and crystallographic studies. The single crystal X-ray diffraction study depicts that molecule is puckered with two aromatic rings lying out-of-plane in near anti-configuration across the C=N bond. The weak interactions involved in supramolecular framework formation are Cl···O, Cl···Cl, Cl···H, Cl···N, C···H, and O···H contacts. The intermolecular O···H interaction being stronger than other dispersive interactions such as halogen bonding, interlocks the molecules in a 2D sheet-type packing. All the structure directing interactions involved in developing crystal architecture are addressed with Hirshfeld surface analysis and fingerprint plots. The energy framework analysis shows visualization of 3D topology of short contacts related to molecular packing of compound I which further clarifies the predominance of both Coulombic and dispersive energies in developing supramolecular architecture.